1994
DOI: 10.1007/bf00563203
|View full text |Cite
|
Sign up to set email alerts
|

Standards for ultrasonographic measurements of the hip joint in Indian adults

Abstract: Synovitis in the hip joint, in contrast to that in other limb joints, is extremely difficult to evaluate clinically. In the hip joint synovitis manifests as an increase in the distance between the iliofemoral ligament and the femoral neck. The present ultrasonographic study was undertaken in 110 healthy Indian adults to establish standards for the depth of the normal hip joint space in the normal Indian adult population. The shortest distance was 4 mm, the longest was 9 mm. The mean distance was 6.4 (S.D. 1.1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Our study totaled 260 quantitative measurements for each articular recess. We observed that, in comparison to other studies, 9,[21][22][23][24][25][26][27] our measurements were similar for most of the recesses, and the differences identified could possibly be attributed to the technology of the equipment and the transducer, scan sites, and sample size, which was greater in our study than in most of the published studies that had identical results. Among the quantitative measurements taken, we observed that particular recesses had discrepant measurements when compared to the limited number of studies found in the literature.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our study totaled 260 quantitative measurements for each articular recess. We observed that, in comparison to other studies, 9,[21][22][23][24][25][26][27] our measurements were similar for most of the recesses, and the differences identified could possibly be attributed to the technology of the equipment and the transducer, scan sites, and sample size, which was greater in our study than in most of the published studies that had identical results. Among the quantitative measurements taken, we observed that particular recesses had discrepant measurements when compared to the limited number of studies found in the literature.…”
Section: Discussionsupporting
confidence: 49%
“…The only other study to stratify a sample by age group was conducted by Ellegaard et al, 6 and despite the lower number of individuals included and the restriction of the assessment to semiquantitative measurements of the small hand joints, their results suggest sex‐ and age‐related differences. Among the works that purported to correlate certain demographic data with articular sonographicmeas‐urements, 9 , 14 , 24 , 26 , 28 only Koski 28 described higher measurements for the elbow in their male volunteers. As suggested in the literature, semiquantitative synovial hypertrophy score of 217 or higher is considered pathologic for the small joints of the hand and foot.…”
Section: Discussionmentioning
confidence: 99%
“…Sada suggested an upper limit of 9 mm. 26 In knee studies, Mielke et al found a smaller diameter of the intercondylar cartilage (mean 2.4 mm v 3.1 mm). This study did not detect popliteal cysts in a normal population owing to lower resolution with older equipment.…”
Section: Discussionmentioning
confidence: 96%
“…; we defined this as “major effusion”. In children, side difference in ultrasonic distance between both hips has more diagnostic value than a large ultrasonic distance alone 14. Therefore, we also defined “asymmetrical effusion” based on only a side difference in ultrasonic distance of 1 mm or more (the most symptomatic hip compared with the other hip).…”
Section: Methodsmentioning
confidence: 99%